Prevention and Treatment of Complications in Proctological Surgery - Pescatori, Mario; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2012)
The volume is authored by a colorectal surgeon with long-standing clinical and scientific experience and is devoted to the management of complications following surgery of the anorectum and the pelvic floor. It is aimed not only at general surgeons, perineologists and, of course, proctologists, but also at gastroenterologists, endoscopists, radiologists and physiotherapists, i.e. those who may be involved in both diagnosis and cure whenever an adverse event, either unpredictable or potentially preventable, causes an intra- or postoperative, early or late, mild or life-threatening complication. Severe bleeding, dehiscence, perforation, anorectal stricture, fecal incontinence, and even caval vein thrombosis, fatal Fournier gangrene and pneumomediastinum may occur after anal surgery. The incidence, pathogenesis prevention and treatment of such events are discussed in detail in 10 chapters with 30 tables, 200 illustrations and more than 1000 references. Both conventional procedures and recent innovations are reported. (3z(BUnforgettable clinical cases (complications with litigation)(3y (Band (3z(BTips and Tricks(3y (Bare sections increasing the appeal of this book. The approach is (3z(Bevidence-based(3y (Band holistic, focusing on anorectal problems while taking into consideration whole body-mental unity$1 (Bshowing, for example, that a non-healing perineal wound may be due to hypo-pituitarism, and failure after a re-intervention may be related to psychological distress.s
Keywords: Medicine; Endocrinology; Surgery; Medicine & Public Health; Proctology; General Surgery